Analisa Gameplay Metric pada Game “Survive Jok” menggunakan unity analytics - riwinoto riwinoto; Alfian Akmal (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2021)
Gameplay Metrics are about measuring a player's habits in a game such as navigation, items, use of abilities, jumping, progress or whatever a player in a game is doing either 2D or 3D. one way to get data for Gameplay Metrics is to use an application that can calculate each interaction between the player and the game being played and can provide data in the form of interaction results for each specified variable. In this case, the author wants to use Unity Analytics in the Unity 3D application to get Gameplay Metrics results to be able to analyze Gameplay in the game. The game used is a game that was created by the author with the title "Survive Jok". This is a 3D isometric game action platform where players must avoid collect the items and enemy to proceed to next level . By using Unity Analytics unity 3D in the game, each game is played, the game will provide data according to the specified variable that calculates every player's progression during game play. The results of this will be used to analyze Gameplay made to evaluate the gameplay that has been made .